Muscarinic receptor drug trihexyphenidyl can alter growth of mesenchymal glioblastoma in vivo - Du, Renfei; Sanin, Ahmed Y.; Shi, Wenjie; Huang, Bing; Nickel, Ann-Christin; Vargas-Toscano, Andres; Huo, Shuran; Nickl-Jockschat, Thomas; Dumitru, Claudia A.; Hu, Wei; Duan, Siyu; Sandalcioglu, I. Erol; et al. (Frontiers in Pharmacology, 2024)
Glioblastoma (GBM) is the most commonly occurring and most aggressive primary brain tumor. Transcriptomics-based tumor subtype classification has established the mesenchymal lineage of GBM (MES-GBM) as cancers with particular aggressive behavior and high levels of therapy resistance. Previously it was show that Trihexyphenidyl (THP), a market approved M1 muscarinic receptor-targeting oral drug can suppress proliferation and survival of GBM stem cells from the classical transcriptomic subtype. In a series of in vitro experiments, this study confirms the therapeutic potential of THP, by effectively suppressing the growth, proliferation and survival of MES-GBM cells with limited effects on non-tumor cells. Transcriptomic profiling of treated cancer cells identified genes and associated metabolic signaling pathways as possible underlying molecular mechanisms responsible for THP-induced effects. In vivo trials of THP in immunocompromised mice carry orthotopic MES-GBMs showed moderate response to the drug. This study further highlights the potential of THP repurposing as an anti-cancer treatment regimen but mode of action and d optimal treatment procedures for in vivo regimens need to be investigated further.